2017
DOI: 10.1021/jacs.7b02708
|View full text |Cite
|
Sign up to set email alerts
|

Iodide-Selective Synthetic Ion Channels Based on Shape-Persistent Organic Cages

Abstract: We report here a synthetic ion channel developed from a shape-persistent porphyrin-based covalent organic cage. The cage was synthesized by employing a synthetically economical dynamic covalent chemistry (DCC) approach. The organic cage selectively transports biologically relevant iodide ions over other inorganic anions by a dehydration-driven, channel mechanism as evidenced by vesicle-based fluorescence assays and planar lipid bilayer-based single channel recordings. Furthermore, the organic cage appears to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 43 publications
5
97
0
2
Order By: Relevance
“…To compare with Kim's highly selective iodide channel based on a porphyrin‐derived covalent organic cage, the same assay conditions used by Kim were applied to 1 a (see Figure S22). The resulting quenching of HPTS fluorescence follows the same selectivity sequence as reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare with Kim's highly selective iodide channel based on a porphyrin‐derived covalent organic cage, the same assay conditions used by Kim were applied to 1 a (see Figure S22). The resulting quenching of HPTS fluorescence follows the same selectivity sequence as reported.…”
Section: Resultsmentioning
confidence: 99%
“…The first iodide channel was reported by the group of Gin and is based on a β‐cyclodextrin, exhibiting low activity and low selectivity among halides (I − >Br − >Cl − ) . Recent work by the group of Kim has shown that a porphyrin‐based covalent organic cage can achieve high I − /Cl − selectivity but with quite moderate iodide transport activity . As such, there is a need to develop highly active and selective artificial iodide transporters for potential medical treatment of IDD.…”
Section: Introductionmentioning
confidence: 99%
“…To date, DCC has been successfully appliedt oar ange of biological templates,i ncluding enzymes, receptors, transmembrane transporters, nucleotides, and polymer-supported targets. [11][12][13][14][15][16][17] However, most, if not all, such biologicallyt emplated DCC approaches employ only as inglet emplate to directt he self-assembly process;t his severelyl imits the applications of DCC approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Large, rigid POCs have the potential to incorporate multiple non-interacting active sites. This broad structural diversity in combination with soluble processing that is not possible with most heterogeneous materials has led to POC applications in gas separation, [16] artificial ion channels, [17] nanoparticle encapsulation, [18] batteries, [19] and supramolecular allostery. [20] The molecular structure of POCs also facilitates post-synthetic modifications where more robust and intricate cages can be obtained.…”
mentioning
confidence: 99%